Locals rule : historical lessons for creating local defense forces for Afghanistan and beyond - Long, Austin G. (Rand Corporation monograph series., 2012)
"Local defense forces have played a key role in counterinsurgencies throughout the 20th century. With the recent development of the Afghan Local Police (ALP) as a major part of the U.S.-led counterinsurgency campaign in Afghanistan, lessons learned from earlier efforts to build local defense have become increasingly salient. This study examines eight cases of local defense forces used in the context of counterinsurgency in Indochina, Algeria, South Vietnam, Oman, El Salvador, Southern Lebanon, Afghanistan, and Iraq. It covers an extensive time period (from 1945 to the present) and geographic scope, as well as a wide range of intervening countries and regimes, including the United States, the United Kingdom, France, Israel, and the Soviet Union. The authors compare the lessons learned from these eight cases and apply them to the current development of the ALP, in order to outline potential challenges and to suggest a way forward that takes into account the historical experience."--P. [4] of cover.